2018
DOI: 10.2147/lra.s175547
|View full text |Cite
|
Sign up to set email alerts
|

Broken needle during spinal anesthesia: an avoidable complication

Abstract: The occurrence of a needle breaking is a very rare complication of spinal anesthesia (SA). We report a case of a broken spinal needle occurring in a morbid obese pregnant woman during SA indicated for an emergent cesarean section. Multiple puncture attempts due to difficult identification of lumbar spine, associated with an inadequate use of the introducer, contributed to this complication. The recognition of predictive factors for difficult neuraxial anesthesia, the use of ultrasound in obese patients, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
4
0
5
Order By: Relevance
“…Patient selection, potential use of larger gauge needles, withdrawing the spinal needle into the introducer prior to redirection, and utilization of ultrasound have all been proposed to reduce the possibility of a broken needle [ 5 ]. Preinsertion lumbar ultrasound has been shown to reduce the number of puncture attempts and increase the success rate of spinal placement in obese patients [ 1 , 7 ]. Chin et al reported a 2 to 1 first-time success rate when performing spinal anesthesia under ultrasound guidance vs. landmarks only in patients with BMI >35 kg/m 2 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient selection, potential use of larger gauge needles, withdrawing the spinal needle into the introducer prior to redirection, and utilization of ultrasound have all been proposed to reduce the possibility of a broken needle [ 5 ]. Preinsertion lumbar ultrasound has been shown to reduce the number of puncture attempts and increase the success rate of spinal placement in obese patients [ 1 , 7 ]. Chin et al reported a 2 to 1 first-time success rate when performing spinal anesthesia under ultrasound guidance vs. landmarks only in patients with BMI >35 kg/m 2 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a known risk factor for cesarean sections (c/s). Increasing BMI has been strongly associated with a higher rate of sections [ 1 ]. Morbidly obese parturients pose many challenges to the anesthesiologist; spinal anesthesia is the preferred anesthetic of choice for c/s to minimize maternal fetal risks associated with general anesthesia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…4. Si se percibe resistencia anormal o contacto óseo, es aconsejable no continuar con la punción, así como tampoco retirar la aguja o cambiar su dirección a través del introductor sin movilizarlo (11) . 5.…”
Section: Consejos Para Prevenirunclassified
“…5. Es esencial, en el caso de pacientes con riesgo de punciones difíciles, considerar el uso de ultrasonido, especialmente después de la primera punción lumbar fallida o, de igual manera, en presencia de factores de riesgo para punción lumbar difícil (11) . 6.…”
Section: Consejos Para Prevenirunclassified
“…La incidencia de ruptura de aguja espinal no esta determinada, aunque se mencione en la literatura el aumento de reporte de casos de esta complicación en la última década, presentándose mayormente en pacientes obstétricas con obesidad [3], [4], [6].…”
unclassified